Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\lnot \forall y: Y.A\vdash \exists y: Y.(A\rightarrow B)$$

Need to prove that LHS entails RHS, however I'm confused as to how to do it. Never used a negation on a universal quantifier before.

Any help would be appreciated.

share|cite|improve this question

HINT $$\lnot \forall y: Y.A \equiv \exists y: \lnot Y.A$$

share|cite|improve this answer
Thanks, I researched on De Morgan's for Quantifiers and figured it out! – user114083 Dec 7 '13 at 11:26

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.